Economic burden of obesity: A systematic review - Hasan Yusefzadeh; Ali Rashidi; Bahlol Rahimi (Wolters Kluwer Medknow Publications, 2019)
Obesity imposes considerably high economic costs on the health-care system. It is proposed that 10% of health-care costs belong to direct and indirect effects of obesity. Taking measures to prevent, manage, and treat obesity is costly. However, some benefits can be obtained by reducing economic costs and by improving health in the future. This study aimed to systematically review the costs caused by obesity. We systematically searched the English language literature indexed in PubMed, Scopus, and Web of Science databases (January 2000 to September 2017). Articles were included if direct and indirect costs of obesity were assessed among participants at the age of more than 18 years. Key terms including economic burden, medical cost, nonmedical cost, and obesity were used for this search. From a total of 20 studies, 9 papers found to be relevant for reviewing. According to these papers, obesity accounts for 31.8% of direct costs (health-care costs related to obesity) and 68.1% of indirect costs (costs related for reducing productivity and production value). Therefore, obese people spend 32% more for medical costs compared to people with normal weight. Due to great number of short-term and long-term complications of obesity and its potential economic impact, efforts are needed to be taken to facilitate health interventions and social policies. Nationally, as obesity imposes high costs on people and health-care system which should fund most of these costs, developing plans to decrease these costs are needed.